2014
DOI: 10.1016/j.msard.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Monocular and binocular low-contrast visual acuity and optical coherence tomography in pediatric multiple sclerosis

Abstract: Background Low-contrast letter acuity and optical coherence tomography (OCT) capture visual dysfunction and axonal loss in adult-onset multiple sclerosis (MS), and have been proposed as secondary outcome metrics for therapeutic trials. Clinical trials will soon be launched in pediatric MS, but such outcome metrics have not been well-validated in this population. Objectives To determine whether MS onset during childhood and adolescence is associated with measurable loss of visual acuity and thinning of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
(26 reference statements)
3
31
0
Order By: Relevance
“…32 The anterior visual pathway has been interrogated in pediatric MS using functional scales (such as low-contrast letter acuity) and structural imaging (with OCT). While decreased lowcontrast letter acuity scores and retinal nerve fiber layer (RNFL) thinning have been demonstrated in pediatric patients with MS with a history of ON, 33 there are conflicting data regarding the relationship between deficits in low-contrast visual function and retinal pathology in the eyes of children with MS unaffected by a clinical attack of ON (MS non-ON eyes). 34,35 One study has shown preserved RNFL in MS non-ON eyes, 33 suggesting that OCT may capture only local thinning after ON.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The anterior visual pathway has been interrogated in pediatric MS using functional scales (such as low-contrast letter acuity) and structural imaging (with OCT). While decreased lowcontrast letter acuity scores and retinal nerve fiber layer (RNFL) thinning have been demonstrated in pediatric patients with MS with a history of ON, 33 there are conflicting data regarding the relationship between deficits in low-contrast visual function and retinal pathology in the eyes of children with MS unaffected by a clinical attack of ON (MS non-ON eyes). 34,35 One study has shown preserved RNFL in MS non-ON eyes, 33 suggesting that OCT may capture only local thinning after ON.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…While decreased lowcontrast letter acuity scores and retinal nerve fiber layer (RNFL) thinning have been demonstrated in pediatric patients with MS with a history of ON, 33 there are conflicting data regarding the relationship between deficits in low-contrast visual function and retinal pathology in the eyes of children with MS unaffected by a clinical attack of ON (MS non-ON eyes). 34,35 One study has shown preserved RNFL in MS non-ON eyes, 33 suggesting that OCT may capture only local thinning after ON. However, 2 other studies have shown decreased RNFL in pediatric MS non-ON eyes, suggesting that OCT might capture a more global degenerative component of MS. 34,35 Further validation of OCT as an outcome in pediatric MS is needed.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…It is important to perform paraclinical testing to evaluate for subclinical disease or for evidence of a prior attack that was not identified-a key issue in young children who may not have reported mild symptoms. Visualevoked responses 22 or optical coherence tomography features 23,24 consistent with prior optic neuritis can be used to support a prior demyelinating event, which in combination with MRI evidence of DIT and DIS can confirm the diagnosis of MS. Further research on the implications of RIS in the pediatric population and consensus regarding management of both children and adults with accrual of new MRI lesions is required.…”
Section: Role Of Mri In Ms Diagnosismentioning
confidence: 99%
“…22 In contrast, another study demonstrated that LCVA was not associated with RNFL thinning after adjusting for age and intereye correlations. 25 Decreases in other functional testing, including color vision and VF, correlate with decreases in RNFL. Replication of these results in other cohorts is needed.…”
mentioning
confidence: 99%
“…14,23,24 Three pediatric studies have demonstrated decreased low-contrast visual acuity (LCVA) after ON. 21,22,25 One study showed a correlation between RNFL thickness and LCVA (using 2.5% Sloan letter charts) for all demyelinating disease eyes (R 5 0.42, p 5 0.002). 22 In contrast, another study demonstrated that LCVA was not associated with RNFL thinning after adjusting for age and intereye correlations.…”
mentioning
confidence: 99%